Tropical fruit descriptors (revised) - International Board for Plant Genetic Resources (International Board for Plant Genetic Resources, 1980)
Working Group to review the Tropical Fruit Descriptors and strategy for collection, evaluation, utilization and conservation, Bangkok, Thailand, 14 - 15 July 1980